Impairments in odour detection and hedonic ratings of unpleasant smells in asymptomatic university students as SARS‐Cov‐2 emerged locally. (6th September 2021) - Walsh‐Messinger, Julie; Kaouk, Sahar; Manis, Hannah; Kaye, Rachel; Cecchi, Guillermo; Meyer, Pablo; Malaspina, Dolores
Abstract: Sudden olfactory loss in the absence of concurrent nasal congestion is now a well‐recognized symptom of COVID‐19. We examined olfaction using standardized objective tests of odour detection, identification and hedonics collected from asymptomatic university students before and as SARS‐CoV‐2 emerged locally. Olfactory performance of students who were tested when the virus is known to be endemic ( n = 22) was compared to students tested in the month prior to viral circulation ( n = 25), a normative sample assessed during the previous 4 years ( n = 272) and those tested in prior years during the same time period. Analyses showed significantly reduced odour detection for the virus exposed cohort compared to students tested before ( t = 2.60; P = .01; d = 0.77; CI 0.17, 1.36) and to the normative sample ( D = 0.38; P = .005). Odour identification scores were similar, but the exposed cohort rated odours as less unpleasant ( P < .001, CLES = 0.77). Hyposmia increased 4.4‐fold for students tested 2 weeks before school closure ( N = 22) and increased 13.6‐fold for students tested in the final week ( N = 11). While the unavailability of COVID‐19 testing is a limitation, this naturalistic study demonstrates week‐by‐week increase in hyposmia in asymptomatic students as a virus was circulating on campus, consistent with increasing airborne viral loads. The specific hedonic deficit in unpleasantness appraisal suggests a deficit in the TAAR olfactory receptor class, which conveys the social salience of odours. Assessment of odour detection and hedonic ratings may aid in early detection of SARS‐CoV‐2 exposure in asymptomatic and pre‐symptomatic persons. Abstract : Participants assessed when SARS‐CoV‐2 was endemic showed significantly reduced odour detection compared to those tested in the prior month, when viral spread was minimal, and compared to a normative sample tested over a 4‐year period. Hyposmia increased 4.4‐fold for participants tested 2 weeks prior to school closure and 13.6‐fold for those assessed in the final week before closure. Odour identification scores did not differ, but the exposed cohort rated unpleasant odours as less unpleasant.